Needs and potential of unmanned vehicles in sewers. Issue 1 (1st February 2016) - Garda, Aude; Castillo, Francisco; Binet, Guillaume; Litrico, Xavier; Gil, Alicia
Abstract : Sewer systems are complex and large structures located under the ground. Their good functioning is a strategic issue which requires regular inspections and maintenance operations. These interventions involve important risks and constraints regarding health and security of operators as well as accessibility to structures and cost of these operations. In this context, unmanned vehicles offer new opportunities to reduce or simplify human interventions in the sewers. As an example, Suez Water Spain has developed a first prototype of unmanned aerial vehicle dedicated to inspection of underground retention tanks and big sewer pipes. The information collected by the drone are automatically integrated into the information system and the decision-making process. Even if the first tests performed with this drone have been successful, there are still a number of pending technological issues that needs to be solved for operational use: positioning, data transmission, trajectory, etc.